Nikolai Gumilev in Dialogue with Innokenty Annensky (“Acteon” and “The Poisoned Tunic”) - Шелогурова, Галина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
In the paper the following issues are discussed: 1. Gumilev’s and Annensky’s dramas in the context of ‘poetic theatre’; 2. Common features of Acteon and Famira-kifared; 3. Points of disagreement between the playwrights (Acteon and The Poisonned Tunic against the background of Famira); 4. The figure of the artist as the protagonist of the dramas under consideration.